Penerapan Sistem Informasi Akuntansi dan Sistem Pengendalian Internal terhadap Keakuratan Persediaan Barang (Studi Kasus CV. Mega Multi Bisnis) - Ardelia, Putri; Novika, Novika; Oktalina, Gayatria (Jurnal IAKP: Jurnal Inovasi Akuntansi Keuangan & Perpajakan, 2024)
The study aims to approved empirically the influence Accounting System Information and Internal Control on accuracy of goods supply warehouse. The scope of this research focuses on the inventory of goods on CV. Mega Multi Business. This study uses a quantitative approach. The data collection technique uses a questionnaire. Distribution of questionnaires was carried out directly and processed and analyzed using linear regression. The results of the first hypothesis test show that the t-count value is greater than t-table (6.835) > ttable (2.002), which shows that the implementation of an accounting information system has a significant effect on the accuracy of inventory. The second hypothesis test also displays the same results, namely the tcount value is greater than ttable (4.065) > (2.002) which indicates that the internal control variable has a significant effect on the accuracy of inventory. The third hypothesis test also shows the same thing, where the t count is greater than the t-table of 0.771; 0.914 and F count greater than F table (27.462 > 3.16), which means that the implementation of the Accounting Information System and Internal Control together has a significant effect on the accuracy of inventory. The conclusion of this research is that the application of accounting information systems and internal control systems has a positive and significant effect on the accuracy of inventory items, both partially and simultaneously.Keywords: Accounting Information System, Internal Control, Inventory